The Cyberspace Anthropology: A Foreword - David Hakken (Antropologi Indonesia, 2004)
"...[...]The volume is introduced with discussion of these mundane details not only because anthropologists are supposed to report context. We also wish to underline the role of AITs as enablers of the discussion of their cultural correlates that follows. While anthropologists have long encouraged global thinking, existing technologies allowed us to act on our thoughts with greater dispatch. We want this issue of JAI to have a similarly reverberating impact, broadening the issues on the agenda of both Indonesianist anthropology and cyberspace ethnography."